D-Allulose (D-Psicose) Biotransformation From Allitol by a Newly Found NAD(P)-Dependent Alcohol Dehydrogenase From Gluconobacter frateurii NBRC 3264 and the Enzyme Characterization - Wen, Xin; Lin, Huibin; Ning, Yuhang; Liu, Guangwen; Ren, Yilin; Li, Can; Zhang, Chengjia; Lin, Jianqun; Song, Xin; Lin, Jianqiang (Frontiers in Microbiology, 2022)
The NAD(P)-dependent alcohol dehydrogenase (ADH) gene was cloned from Gluconobacter frateurii NBRC 3264 and expressed in Escherichia coli BL21 star (DE3). The expressed enzyme was purified and the characteristics were investigated. The results showed that this ADH can convert allitol into D-allulose (D-psicose), which is the first reported enzyme with this catalytic ability. The optimum temperature and pH of this enzyme were 50 ℃ and pH 7.0, respectively, and the enzyme showed a maximal activity in the presence of Co2+. At 1 mM Co2+ and allitol concentrations of 50, 150, 250 mM, the D-allulose yields of 97, 56 and 38%, respectively, were obtained after reaction for 4 h under the optimal conditions, which was much higher than that obtained by using epimerase method of about 30%.